(untitled) (Razi Medical Journal, 2025)
Acute mechanical bowel obstruction is a common intra-abdominal surgical emergency, accounting for 12–16% of acute abdominal pain cases. Despite advances in diagnostics and surgical techniques, it remains a major clinical challenge due to varied causes and presentations. Both small and large bowel obstructions often require urgent, individualized management. This retrospective observational study reviewed 60 adult patients (aged >14 years) admitted with acute intestinal obstruction at Misurata Medical Center between March 2022 and February 2023. Paralytic ileus cases were excluded. Data included demographics, prior surgeries, clinical features, investigations, and treatment outcomes. Of the 60 patients, 37 (61.7%) underwent surgery, while 23 (38.3%) were managed conservatively. The male-to-female ratio was 1.85:1, with the majority (81%) aged 20–40 years. Abdominal pain was the predominant symptom (95%), followed by vomiting (70%), constipation (55%), distension (46.7%), and obstipation (15%). A significant proportion (63.3%) had prior abdominal surgery, mainly war-related laparotomies. Adhesions and fibrous bands were the leading cause (58.3%), followed by obstructed hernias (26%), malignancies (10%), volvulus (3.3%), and primary peritonitis (1.7%). Conservative management was successful in 23 patients, but surgical intervention was required in most cases due to complications or lack of improvement. Intraoperative findings guided procedures: obstructed hernias with gangrene required resection and anastomosis with hernia repair; malignant obstructions were treated with resection, bypass, or stoma formation, followed by oncologic referral; adhesive obstructions were managed with adhesiolysis, with resection if bowel viability was compromised; volvulus was treated with resection and either primary anastomosis or Hartmann’s procedure.